Changes in Opioid Prescribing Following the Implementation of State Policies Limiting Morphine Equivalent Daily Dose in a Commercially Insured Population. Issue 9 (September 2021) - Heins, Sara E.; Castillo, Renan C.
Abstract : Background: Prescription opioid mortality doubled 2002–2016 in the United States. Given the association between high-dose opioid prescribing and opioid mortality, several states have enacted morphine equivalent daily dose (MEDD) policies to limit high-dose prescribing. The study objective is to evaluate the impact of state-level MEDD policies on opioid prescribing among the privately insured. Methods: Claims data, 2010–2015 from 9 policy states and 2 control states and a comparative interrupted time series design were utilized. Primary outcomes were any monthly opioid use and average monthly MEDD. Stratified analyses evaluated theorized weaker policies (guidelines) and theorized stronger policies (passive alert systems, legislative acts, and rules/regulations) separately. Patient groups explicitly excluded from policies (eg, individuals with cancer diagnoses or receiving hospice care) were also examined separately. Analyses adjusted for covariates, state fixed effects, and time trends. Results: Both guideline and strong policy implementation were both associated with 15% lower odds of any opioid use, relative to control states. However, there was no statistically significant change in the use of high-dose opioids in policy states relative to control states. There was also no difference in direction and significance of the relationship among targeted patient groups. Conclusions: MEDD policies were associated with decreased use of any opioids relative to control states, but no change in high-dose prescribing was observed. While the overall policy environment in treatment states may have discouraged opioid prescribing, there was no evidence of MEDD policy impact, specifically. Further research is needed to understand the mechanisms through which MEDD policies may influence prescribing behavior. Abstract : Supplemental Digital Content is available in the text.